Relação entre estresse, alterações na parede celular, metabólitos e acúmulo de metais nas galhas induzidas em Macairea radula (Melastomataceae) - Santos, Patrícia Dias (2024)
Plants are affected by biotic and abiotic stresses, which can influence their growth, development, productivity and geographic distribution. For survive adverse environmental conditions, developed adaptive strategies such as metabolites accumulation with protective functions, mainly against herbivore attacks. Many of these organisms, especially insects, induce biotic stress in plants by species-specific parasitism relationship, which can alter plant metabolism and, to induce anomalous growth with hyperplasia and cellular hypertrophy, leading to gall formation. These structures are controlled by reactive oxygen species release, enzymes, carbohydrates, secondary compounds, phytohormones; and can also accumulate metals in the host plants tissues. It is probable that molecules biosynthesis may change throughout the day, following a circadian cycle in response to biotic stress. In this context, this thesis has as its central hypothesis that the greater the oxidative stress in gall tissues, the greater the primary and secondary metabolites accumulation, mediated by the high phytormone concentration and metals to maintain and protect the insect-plant relationship and, possibly, increase the chances of interaction with other organisms, such as natural enemies. The thesis is divided into five chapters, a general introduction, final conclusions and perspective. In the first chapter, I show the changes in the cell wall polysaccharides compositions in the reserve and nutritive tissues of galls induced by Palaeomystella oligophaga (Lepidoptera) in Macairea radula (Melastomataceae) in the diferent development galling insect stages. In the second chapter, I present monosaccharides variation to test the hypothesis that in galls with diferent colors and in the natural enemies presence, the monosaccharide composition is more abundant and diverse compared to non-galled tissues in M. radula. In the third chapter, I present the antioxidant enzymes, primary and secondary metabolites relationship found in galled tissues in the presence or absence of natural enemies compared to non-galled tissues and their ecological implications. In the fourth chapter, I show the relationship of polyamines, phytorhormones and metals accumulation with the galls coloration in the oxidative stress dissipation. Finally, in the fifth chapter, I present a thesis summary topics with a circadian cycle approach to explain how plants can be in synchrony with galling insects in the metabolites production, especially carbohydrates. In this thesis, the cell wall composition changes in the gall compartments in according to the the galling insect development stage, especially in relation to homogalacturonans and xyloglucans, as well as the greater amount of glucose and galactose in the galls, which support the high metabolism and availability of resources to the galling herbivore; and the phenolic acids, flavonoids and hydrolyzable tannins presence, mainly in the larval stage wherein greater activity of the enzymes CAT and PAL was also detected. Other molecules, such as polyamines, were more abundant in red galls than in green galls. And the levels of the hormones ABA, GA3, IAA and ACC were higher in green galls than in red galls, while SA and MeJA were more abundant in red galls. These results were associated with the Al, Fe, Pb and Cu accumulation in red galls than in green galls, which may be related to their translocation and biosynthesis of phenolic chelating compounds to reduce the toxicity of these metals, transforming them into less toxic forms for the galls to maintain the red coloration as a form of protection against the galling insect and its natural enemies.